UNREPORTED FEMINIST ISSUES IN THAILANDS SOUTHERN UNIREST - Sakiroh Yaena Benharoon (The Indonesian Journal of Communication Studies, 2014)
This study aims to examine unreported issues on feminist in Thailand’s southern unrest, and to explore their newsworthiness. In-depth interviews and focus group discussions of groups of academic experts, NGOs staffs, stringers and local news reporters, victims of the ongoing unrest, and youths in the area were conducted over a period of five months, starting from October 2010 to February 2011. This is to provide the data on what characteristics of information and stories relating to feminist that the key informants consider worth reporting during the crisis. The findings reveal that twelve unreported topics on feminists include (1) continuous aids and compensation for female victims, (2) ways to cope with the crisis, (3) government policy and solutions affecting females, (4) transformation of women’s roles, (5) female participation in resolving problems and peace-building, (6) women’s attitudes towards the southern unrest and possible ways out, (7) women’s rights and roles in Islam, (8) women rights and gender equality, (9) women and education, (10) women and motherhood, (11) women’s quality life and sexual violence, and (12) other issues relating Muslim women and their way of life, working women, women and social roles, women as career leaders, women as wives behind husbands’ success, women as successful mothers, female reproductive issues, and women and the mass media. In addition, what should be dressed in the media include issues on (1) women working for social benefits, (2) women’s participation in making a better society, (3) women applying religious knowledge to daily life, (4) women as roles model, (5) women behind family’s success, and (6) educated women.